Modelling and development of a vibration-based electromagnetic energy harvester for industrial centrifugal pump application. (August 2017) - Gilani, Syed Faizan-ul-Haq; Khir, Mohd Haris bin Mohd; Ibrahim, Rosdiazli; Kirmani, Emad ul Hassan; Gilani, Syed Ihtsham-ul-Haq
Abstract: This paper reports a unique vibration-based electromagnetic energy harvester (VEH) designed to power wireless sensors used for fault monitoring of industrial centrifugal pumps. The design consists of two independent moving parts; the central part and the outer part. The uniqueness of the VEH design exists in its ability to produce higher relative velocity between its two moving parts by isolating vibration from the outer part. The developed prototype produced an open-loop voltage of 3.48 V and a closed-loop voltage of 1.63 V for an optimum load of 700 Ω. This constituted for an average power of 3.8 mW delivered to the load at a natural frequency of 200 Hz and an excitation level of 1 g. The experimentation results were in good agreement with the simulation results as the average percentage error was within an acceptable range of 6.15%. A case study is also presented whereby a ZigBee transceiver is successfully powered from the output generated by the VEH.